2019
DOI: 10.1167/19.14.26
|View full text |Cite
|
Sign up to set email alerts
|

Competition between salience and informational value for saccade adaptation

Abstract: What we see is influenced by where we look. When confronted with multiple relevant targets, inaccurate saccade target selection can impair perceptual performance. Here we ask whether endpoint selection can be optimized by the mechanism maintaining saccade accuracy: saccade adaptation. Therefore, we introduce a double-target adaptation task, where a presaccadic peripheral stimulus (plaid) splits vertically into its two components (Gabor patches) during horizontal saccades. While both targets were task-relevant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…The previous remarks on the neural basis of delayed motor learning, as observed in our paradigm, assume that saccade adaptation to task-relevant stimuli is based on the same core mechanism as saccade adaptation elicited by intra-saccadic target steps 4 . So far, there are only a few behavioral studies on saccade adaptation to task-relevant stimuli 23 , 24 , 63 (for a review, see 6 ). Although some recent studies pointed out that, besides the cerebellum, higher cortical areas might contribute to saccade adaptation in general 64 , 65 , there is no physiological data specifically on task-driven saccade adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…The previous remarks on the neural basis of delayed motor learning, as observed in our paradigm, assume that saccade adaptation to task-relevant stimuli is based on the same core mechanism as saccade adaptation elicited by intra-saccadic target steps 4 . So far, there are only a few behavioral studies on saccade adaptation to task-relevant stimuli 23 , 24 , 63 (for a review, see 6 ). Although some recent studies pointed out that, besides the cerebellum, higher cortical areas might contribute to saccade adaptation in general 64 , 65 , there is no physiological data specifically on task-driven saccade adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…2c ). This indicates that without a behavioral goal, it is the default to select salience (Schütz et al, 2012 ; Wolf, Wagner, & Schütz, 2019 ), and this default bias does not decay over time but needs to be actively suppressed (Gaspar & McDonald, 2014 ; Gaspelin, Leonard, & Luck, 2015 ) when salience and behavioral goals compete. In contrast to that, Donk and van Zoest ( 2008 ) found that correct saccade selection decreased with increasing latency when participants had to select the most salient target.…”
Section: Discussionmentioning
confidence: 99%
“…While the latencies of saccadic eye movements are facilitated by the introduction of a perceptual task (Bieg et al., 2012; Montagnini & Chelazzi, 2005; Trottier & Pratt, 2005), they are not modulated by uncertainty in the stimulus (Wolf & Schütz, 2017). The sensorimotor adaptation of saccades is sensitive to a perceptual task (Schütz et al., 2014) and to some extent also to perceptual uncertainty (Gerardin et al., 2015; Wolf et al., 2019). In visual search, eye movements minimize uncertainty and maximize information gain under some conditions (e.g., Najemnik & Geisler, 2005; Peterson & Eckstein, 2012) but not under others (e.g., Nowakowska et al., 2017; Verghese, 2012).…”
Section: Discussionmentioning
confidence: 99%